2018
DOI: 10.1017/s0263034618000149
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dominated implosion with nano-plasmonics

Abstract: Inertial Confinement Fusion is a promising option to provide massive, clean, and affordable energy for humanity in the future. The present status of research and development is hindered by hydrodynamic instabilities occurring at the intense compression of the target fuel by energetic laser beams. A recent proposal by Csernai et al. 1 combines advances in two fields: detonations in relativistic fluid dynamics and radiative energy deposition by plasmonic nano-shells. The initial compression of the target pellet … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…The recent paper of Csernai et al (2018) commented here is even more problematic in this respect. The authors carried out calculations for an uncompressed ball heated by external radiation.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…The recent paper of Csernai et al (2018) commented here is even more problematic in this respect. The authors carried out calculations for an uncompressed ball heated by external radiation.…”
mentioning
confidence: 78%
“…Thus, the visible radiation will not penetrate into the depth of the target, but it will be absorbed within the underdense plasma and the skin layer of the generated plasma. Csernai et al (2018) assume a constant opacity during the whole process, and they do not take into account the variation of opacity during the heating process and hot plasma formation. 5.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The direction and importance of those variations critically depends on the reactants and plasma conditions, as can be seen by comparing equations (20), (40) and (42). In particular, it was found that primary (and beambeam) reactions are hindered by the analyzed environment, while secondary (and beam-target) 16 10 −6 fusions are moderately enhanced. Rate and average cross-section enhancement factors (ratios of screened to bare quantities) were explicitly computed for primary reactions between identical reactants.…”
Section: Discussionmentioning
confidence: 98%
“…An inertial confinement fusion (ICF) plasma (see e.g. the introductory book [1] or papers as [12,13,14,15,16,17,18,19]) is obtained by irradiating a target, either solid or enclosed in an external shell, containing fuel for the purported fusion reaction, with several laser beams. Electrons in the target surface receive the photons energy and subsequently accelerate also ions.…”
Section: Non-neutral Laser-induced Plasmas For Fusion Energy Productionmentioning
confidence: 99%